2009
DOI: 10.1210/jc.2008-2189
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Clinical Spectrum in Hepatocyte Nuclear Factor 1B-Maturity-Onset Diabetes of the Young

Abstract: The clinical data of our cases enlarge the wide spectrum of patients with HNF1B anomaly. The underlying molecular defect in all cases was a 1.3- to 1.7-Mb deletion, and paired, segmental duplications along with breakpoints were most likely involved in this recurrent chromosomal microdeletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 20 publications
5
85
1
2
Order By: Relevance
“…The difference in clinical presentation of the HNF1β mutation is thought to be caused by the differences in HNF1β activity in conjunction with the repression of HNF1α activity in selected promoters and tissues [8]. Raile et al, suggested that gene dosage of other genetic factors and/or environmental triggers could play a role in the pattern and severity of the HNF1β-associated MODY [9]. Due to the rarity of patients with HNF1β mutation, the clinical manifestations and correlation with gene mutations are not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The difference in clinical presentation of the HNF1β mutation is thought to be caused by the differences in HNF1β activity in conjunction with the repression of HNF1α activity in selected promoters and tissues [8]. Raile et al, suggested that gene dosage of other genetic factors and/or environmental triggers could play a role in the pattern and severity of the HNF1β-associated MODY [9]. Due to the rarity of patients with HNF1β mutation, the clinical manifestations and correlation with gene mutations are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 47 individuals have been reported with liver disease associated with HNF1β gene defects, 25 as case reports [6,[8][9][10][11][12][13][14] and 22 identified in patients with the known renal disease being screened for HNF1β defects [15][16][17]. Liver involvement may present as cholestasis, elevated liver enzyme levels (ALT and/or GGT), hepatomegaly, or steatosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations